Studi Historika terhadap Dwi Natur Kristus: Yesus Allah Sejati dan Manusia Sejati - Beny Christison Bantara; Natalia Natalia (Jurnal Arrabona, 2024)
The two natures of Christ are something that goes beyond human logic because how is it possible to have two natures in a person at the same time, namely Jesus being a true God and a true man, without any mixing? The aim of writing this article is to provide an understanding with a historical approach to the nature of Christ, which has been the subject of debate by theological scholars so far, by using qualitative research methods through research into the history of church development, explaining the views of heretics who rejected the nature of Christ as true God and true man, and also explaining the reason why Jesus used two natures when he came to earth. This article ends with the conclusion that the anti-Christ group will not end before the end of time; this group will continue to mislead God's chosen people. Because of that, the church continues to play an active role in providing correct teachings based on the Bible, which is God's Word as the absolute truth, as the basis for those who are strong in the growth of strong faith in this world full of error.